Leaching of Chromium, Copper, and Arsenic from CCA-Treated Utility Poles - Cynthia A. Coles; Joseph A. Arisi; Marion Organ; Geoff I. Veinott (Applied and Environmental Soil Science)
Concentrations of Cu, Cr, and As in soils surrounding 26 Douglas Fir Chromated Copper Arsenate (CCA) treated utility poles and in rainwater runoff from a new CCA treated utility pole segment (log) suspended outside in a cylinder were studied. The age of the utility poles, distances from the poles, rainfall amounts, and characteristics of soil samples including cation exchange capacity (CEC), pH, and total organic carbon (TOC) were considered. Heavier rainfall, damp conditions, and more weathered poles contributed to the greatest leaching of Cu, Cr, and As. The maximum measured soil concentrations of Cu, Cr, and As were 37.5, 65.5, and 38.9 mmol/kg and maximum Cu, Cr, and As concentrations in rainwater run-off were 14, 77.7 and 55.8 μmol/L. Metal concentrations decreased with distance from the poles and, except at one utility pole location, Cu was the most leached of the three elements. The As appeared to have greater mobility in the soil than the Cr. Along the transmission line nearest the coast and from which the greatest amount of samples was collected, soil CEC and TOC values were the highest and the CEC and TOC were directly and strongly correlated.